2015
DOI: 10.1161/atvbaha.115.306573
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Deletion of the Type II Transforming Growth Factor-β Receptor in Smooth Muscle Cells Causes Severe Aortopathy in Mice

Abstract: Objective Prenatal deletion of the type II TGF-β receptor (TBRII) prevents normal vascular morphogenesis and smooth muscle cell (SMC) differentiation, causing embryonic death. The role of TBRII in adult SMC is less well studied. Clarification of this role has important clinical implications because TBRII deletion should ablate TGF-β signaling and blockade of TGF-β signaling is envisioned as a treatment for human aortopathies. We hypothesized that postnatal loss of SMC TBRII would cause aortopathy. Approach a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
134
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(156 citation statements)
references
References 56 publications
6
134
2
Order By: Relevance
“…It is worth noting that the outer laminae orientation of ascending aortic pathology is not a unique feature in Ang II-infused mice. This feature has been frequently observed in many animal models in which ascending aortic aneurysmal diseases are provoked by a wide variety of stimuli (7,(15)(16)(17). Of clinical relevance, the predominance of pathology in the outer medial layers is also a common feature in human ascending aortic aneurysm and dissection (14,18).…”
Section: Commentarymentioning
confidence: 82%
“…It is worth noting that the outer laminae orientation of ascending aortic pathology is not a unique feature in Ang II-infused mice. This feature has been frequently observed in many animal models in which ascending aortic aneurysmal diseases are provoked by a wide variety of stimuli (7,(15)(16)(17). Of clinical relevance, the predominance of pathology in the outer medial layers is also a common feature in human ascending aortic aneurysm and dissection (14,18).…”
Section: Commentarymentioning
confidence: 82%
“…11, 12 In addition, we recently reported that loss of physiologic TGF-β signaling in aortic smooth muscle cells (SMC) of young mice caused significant abdominal aortic dilation and inflammation. 13 Taken together, the preponderance of experimental data support a protective role for TGF-β in AAA development and suggest that this protective role might be exploited for the development of human therapies.…”
mentioning
confidence: 97%
“…In contrast, our study suggests that disruption of TGF-β signaling that is confined to SMC is sufficient to cause medial cell loss, aortic dilation, and inflammatory cell infiltration in the aortic wall. 13 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19 Our own group found that loss of VSMC TGF-β signaling by type II TGF-β receptor deletion caused medial thinning in abdominal aortas of angiotensin II-infused mice. 20 Viral vector-mediated overexpression of TGF-β1 stabilized AAA in an animal xenograft model. 21 Therefore, all studies except one support a protective role for TGF-β in animal models of acute AAA formation.…”
mentioning
confidence: 99%